THE IMPORTANCE OF THE PASTEUR INSTITUTE IN NOVI SAD FOR THE PREVENTION AND CONTROL OF RABIES IN THE REPUBLIC OF SERBIA - Gazibara, Dragana; Ključar, Marko; Simin, Verica; Bogdan, Ivana; Mijatović, Dragana; Stojšić, Andrea (HEALTH CARE, 2025)
Rabies is a deadly zoonotic disease that occurs in more than 150 countries and represents a public health issue for over three billion people worldwide. In Europe, rabies in animals is present in Ukraine, Belarus, Poland, Moldova, Russia, and Romania, with isolated cases reported in other countries as well. The highest number of human rabies cases is found in Asia and Africa. The aim of this review paper is to present the significance of the Pasteur Institute in Novi Sad in the control and prevention of rabies in the Republic of Serbia. Data for this paper were collected from various databases (Web of Science, PubMed, Google Scholar), bulletins, etc. The Pasteur Institute in Novi Sad is the National Reference Health Institution for rabies in the Republic of Serbia. All activities necessary in the fight against rabies are covered within this institution: providing anti-rabies protection to people at risk of rabies through the administration of cell culture rabies vaccines and human rabies immunoglobulin (HRIG); preventive immunization of high-risk populations; providing expert methodological assistance and professional supervision of the work of 27 anti-rabies stations (ARS) in the Republic of Serbia; supplying HRIG and rabies vaccines to all ARS; establishing doctrinal and professional medical guidelines in the field of anti-rabies protection; monitoring the occurrence of rabies; preparing reports and informing ARS and government authorities about every registered case of rabies in the country; proposing and implementing measures for its control; diagnosing rabies within the national reference laboratory for rabies; and controlling the achieved immunity following the immunization of people and animals. The regional project of oral vaccination of foxes against rabies has been implemented in the territory of the Republic of Serbia since 2010, and monitoring of vaccination effectiveness has been conducted since 2011. In the Republic of Serbia, urban rabies was eliminated in 1980, as was the last case of human rabies in the territory of the province of Kosovo and Metohija, while the last case of sylvatic rabies in foxes in Serbia was registered in 2018. In order to eradicate rabies, synchronized activities of the health and veterinary services are necessary, as well as cooperation at the local, national, and international levels.
Keywords: Pasteur Institute, rabies, history, epidemiology, public health, immunization